Interview of Sayed Z. El-Sayed by Brian Shoemaker - El-Sayed, Sayed Z. (Sayed Zakaria), 1926- (Byrd Polar Research Center Archival Program, 2006)
Dr. Hussein Fausi, pp. 2 Professor Abdel Fatah Mohammed, pp. 2 Dr. Richard Van Cleef, pp. 3 Dr. Richard Flemming, pp. 3 Haupt ______, pp. 3 Ravel _______, pp. 3 Shepard ______, pp. 3 Claude du Bear, pp. 3 Walter Monk, pp. 3 Peter Ray, pp. 3 Captain Luis R. Capurro, pp. 6-7 Byunig Don Lee, pp. 8, 22 Dr. Martin Johnson, pp. 9 Captain Canepa, pp. 9-10 Larry Gould, pp. 10 ______Zumberg, pp. 10 Lee Washbrun, pp. 10 George Llano, pp. 10, 15, 23-24, 30 Professor Mosby, pp. 12 Richard Thornton, pp. 13 _______Allsion McQueeny, pp. 15 Dr. Morita, pp. 15, 23 Claude Zumell, pp. 16 Holm Henson, pp. 16, 23 Larry Weber, pp. 19 _______Filchner, pp. 22 _______Shackelton, pp. 22 Mary Alice ________, pp. 22-23 George Knox, pp. 28 Dr. Numoto, pp. 29 Lou de Galle, pp. 29 Dick Laws, pp. 29, 37, 42, 64, 66 Joe Farnham, pp. 34, 63 Carol ________, pp. 35 Todd ________, pp. 40 Lubimora ______, pp. 40 Professor Bogdanor, pp. 41 __________ Kryzechevski, pp. 42 Barry Heywood, pp. 42, 65 David Drury, pp. 43 Martin Johnson, pp. 46 Carl Stegan, pp. 54 Sherwood Roland, pp. 55 Mario Mornina, pp. 55 Paul Ramsey, pp. 55-56 Bob Stephenson, pp. 60 Paul Skelly Powers, pp. 60 Charlie Inge, pp. 60 _________ Hovis, pp. 60 Emil Anderson, pp. 61 Admiral Bill Ramsey, pp. 62 Dean Stockwell, pp. 62 Bernard Stonehouse, pp. 64 Bob Abel, pp. 67 Dr. El-Sayed was born in Alexandria, Egypt. After secondary school, he went to the University of Alexandria for his B.S. (1949) in Oceanography. After his M.S., he went to the Scripps Institute of Oceanography on a Fulbright Fellowship. He received his PhD from the University of Washington. As professor emeritus at Texas A & M, he directs a project with the Cooperative Marine Research Program in the Middle East. A friend asked him to work on a biological project on Drake Passage, Antarctica. He worked for several years on vessels from Argentina and was later assigned to a ship for the study of krill. The science team included specialists interested in different aspects of the ecosystem. This was the first of many ...